2016
DOI: 10.18632/oncotarget.7942
|View full text |Cite|
|
Sign up to set email alerts
|

MMP-13 is involved in oral cancer cell metastasis

Abstract: The oral cancer cell line OC3-I5 with a highly invasive ability was selected and derived from an established OSCC line OC3. In this study, we demonstrated that matrix metalloproteinases protein MMP-13 was up-regulated in OC3-I5 than in OC3 cells. We also observed that expression of epithelial–mesenchymal transition (EMT) markers including Twist, p-Src, Snail1, SIP1, JAM-A, and vinculin were increased in OC3-I5 compared to OC3 cells, whereas E-cadherin expression was decreased in the OC3-I5 cells. Using siMMP-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…Deraz et al [32] revealed that the overexpression of MMP-10 could promote the invasion and metastasis of head and neck squamous cell carcinoma, and invasion driven by MMP-10 is possibly associated with p38 MAPK inhibition. It has been reported that MMP-13 could promote the invasion, migration, and adhesion abilities of oral cancer cells [33]. The abnormal expression of MMP-7 has been found to be closely related to the biological behaviour of OSCC, and MMP-7 may be Note: the miRNA names in red color are validated using qRT-PCR induced by COX-2 to contribute to the invasion and metastasis of OSCC [34].…”
Section: Discussionmentioning
confidence: 99%
“…Deraz et al [32] revealed that the overexpression of MMP-10 could promote the invasion and metastasis of head and neck squamous cell carcinoma, and invasion driven by MMP-10 is possibly associated with p38 MAPK inhibition. It has been reported that MMP-13 could promote the invasion, migration, and adhesion abilities of oral cancer cells [33]. The abnormal expression of MMP-7 has been found to be closely related to the biological behaviour of OSCC, and MMP-7 may be Note: the miRNA names in red color are validated using qRT-PCR induced by COX-2 to contribute to the invasion and metastasis of OSCC [34].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the general notion that collagenases (MMP1, MMP8 and MMP13) are key players in cancer biology [27][28][29], relatively little is known about collagenases in PDAC. Although MMP-1 is consistently shown to be overexpressed in PDAC patients compared to healthy controls [30][31][32][33][34][35][36], its effects on cancer progression are inconsistent ( Table 1).…”
Section: Collagenases In Pdacmentioning
confidence: 99%
“…The role of MMPs as EMT inducers has been described in kidney, lung, ovary, oral, and mammary epithelium [52][53][54][55][56][57]. Their mechanism of action involves the processing and activation of pro-TGF-β in the ECM, as well as the direct proteolysis of E-cadherin [53,55,57].…”
Section: The Epithelium To Mesenchymal Transitionmentioning
confidence: 99%